Bactericidal activity of copper-ascorbic acid mixture against Staphylococcus aureus spp. (May 2020) - Gyawali, Rabin; Zimmerman, Tahl; Aljaloud, Sulaiman O.; Ibrahim, Salam A.
Abstract: The purpose of this study was to investigate the bactericidal activity of copper (Cu, 10 ppm) and ascorbic acid (AA, 0.3% v/v) mixture against Staphylococcus aureus ( S. aureus ) ATCC 25923 (methicillin-susceptible) and ATCC 700698 (methicillin-resistant) strains. Approximately 5.5 log10  CFU/ml of each strain was individually inoculated into brain heart infusion (BHI) broth containing Cu, AA, and a Cu-AA mixture, and a time-kill assay was conducted to assess the bactericidal activity. In order to determine the efficacy of Cu-AA mixture as a surface decontaminating solution, the cells were first attached to glass slides (~6.5–7.5 log10  CFU per slide) and treated with a Cu-AA mixture for 1 min. The inner membrane permeability of the S. aureus strains was determined by measuring β-Galactosidase activity. Similarly, changes in the protein profile of treated bacterial cells were analyzed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE). The time-kill study revealed >3.0 log10  CFU/ml reduction in both strains within 24 h of incubation at 37 °C. Attached cells on glass slides were also reduced by > 3.0 log10  CFU per slide after 1 min of exposure to the Cu-AA mixture. The results indicate that the Cu-AA mixture was bactericidal against S. aureus strains and the damage to the inner cell membrane could be attributed to this effect. Graphical abstract: Image 1 Highlights: The presence of Staphylococcus aureus on food contact surfaces is a potential hazard. A mixture of copper (Cu) and ascorbic acid (AA) (vitamin C) kills 99.9% of S. aureus strains. Cu-AA mixture could be a promising substitute for conventional antimicrobial wash solutions. Cu-AA could be used as a novel disinfectant for decontamination of foods and food contact surfaces.